"It Tastes Like Order": Psychotic Evidence for Antipsychotic Efficacy and Medicated Subjectivity. (28th March 2019) - D'Arcy, Michael
Abstract: What counts as evidence in contemporary debates about antipsychotic efficacy? Current research in the fields of psychiatry, public health, and the social sciences continues to cast doubt upon the efficacy of antipsychotic medications, but patient testimonies illuminating the intersection of psychotic experience and the psychiatric injunction to adhere are largely missing from research about psychotropic medications' intended and actually reported effects. Drawing on ethnographic fieldwork in an inpatient psychiatric ward and the community mental health network of Dublin, Ireland, this article explores the ways in which mental health patients are actively engaged in an ongoing process of experimenting with their psychopharmaceuticals, often in the pursuit of an idiosyncratically medicated subjectivity. Joining larger debates about the epistemologically plural nature of evidentiary claims regarding psychopharmaceutical efficacy, this article seeks to foreground the dialogue between clinicians and patients, the latter of whom offer invaluable insights regarding the experience of living with psychosis.